First experience of participation in post-Soviet parliamentary elections in Nizhny Novgorod region: pages of political history - Ya. S. Zanozina; V. M. Plitkina; A. A. Fomenkov (Омский научный вестник: Серия "Общество. История. Современность")
The article is devoted to an important event in the political history of post-Soviet Russia, namely the first parliamentary elections in its history. The aim of the work was to determine the specifics of the results of the first elections of deputies of the Russian Parliament after the collapse of the USSR in the Nizhny Novgorod region. The tasks of the work are related to the study of the elections of deputies of the State Duma (both by single-mandate districts and by party lists), and the Federation Council. A number of conclusions are drawn regarding the political sympathies of residents of different administrative-territorial units of the Nizhny Novgorod region in the first half of the last decade. A kind of Nizhny Novgorod «red belt» is defined geographically, consisting of the southern districts of the region, as well as several districts of the north and east of the region, where voters mostly supported the left. It is revealed that the level of political activity in the elections is quite high, which is not surprising in view of the intense political life during the perestroika period in Gorky, and then in Nizhny Novgorod